School Counselors Involvement and Opportunities to Advocate Against Racialized Punitive Practices - Edwin Hernandez; Enrique Espinoza; Jewel Patterson (Teaching and Supervision in Counseling, 2021)
Given the increase of violence against Black, Indigenous, People of Color (BIPOC), there is no doubt a need to tackle racialized violence in schools. This phenomenological study draws on semi-structured interviews with school counselors to explore their experiences and practices to disrupt the racialized disciplinary practices that disproportionally target Black, Indigenous, and Students of Color. We draw on theories of racialized organizations and organizational routines to better understand how school counselors make sense of their practices in racialized disciplinary practices that dehumanize and criminalized youth of color. Findings from this study revealed two themes: 1) school counselors’ perceived neutrality towards disciplinary practices and 2) school counselors’ advocacy in racialized school discipline practices. This study offers some implications for professional school counseling organization, counselor educators, and school counselors to inform their anti-racist pedagogy to dismantle racialized punitive practices in schools.
Keywords: School Counselors; Organizational Routines; School Discipline